Modelling of pneumatic muscle actuator using Hill's model with different approximations of static characteristics of artificial muscle - Piteľ Ján; Tóthová Mária (MATEC Web of Conferences, 2016)
For modelling and simulation of pneumatic muscle actuators the mathematical dependence of the muscle force on the muscle contraction at different pressures in the muscles is necessary to know. For this purpose the static characteristics of the pneumatic artificial muscle type FESTO MAS-20-250N used in the experiments were approximated. In the paper there are shown some simulation results of the pneumatic muscle actuator dynamics using modified Hill's muscle model, in which four different approximations of static characteristics of artificial muscle were used.